Apakah Work Environment, Work Motivation dan Self Efficacy Berpengaruh Terhadap Employee Performance - Hidayatullah, Fajar; Tiarapuspa, Tiarapuspa (Rifa'Institute, 2023)
The purpose of this study is to analyze whether the Work Environment, Work Motivation, Self efficacy affect employee performance in textile company employees in Jakarta. Data were collected from two hundred and two textile company employees in Jakarta with the data collection technique used was a purposive sample. The test hypothesis used in this study is Structural Equation Modeling (SEM). The results of testing the hypothesis in this study indicate the positive influence of the Work Environment, Work Motivation, Self-Efficacy on Employee Performance. The managerial implication in this study is how companies must add available work facilities to increase employee performance activities to be more productive so that company goals are achieved, managers must also provide more motivation to employees to do the job properly according to production targets, managers must also trust employees more so that can perform most of the tasks very well so that the company's goals are achieved, managers must also be more able to control the performance of their employees in order to produce performance that is in accordance with the goals of textile companies.